Temperament ratings by parents and teachers as predictors of non-verbal ability in Argentinean preschoolers - (:unkn) unknown (Wiley, 2024)
Child temperament is a predictor of non-verbal ability (i.e. thinking and problem-solving skills that do not fundamentally require verbal language production and comprehension). Given that temperament scores might vary depending on whether the reporter is a parent or a teacher, this study analyses (a) whether those reports are different and (b) how each report predicts child non-verbal ability in a non-western, educated, industrialized, rich and democratic sample. The Matrix subtest of KABC-II (a non-verbal ability task widely used in non-western, educated, industrialized, rich and democratic contexts) was administered to 85 Argentinian children (47 girls, 38 boys) aged 4–5 years, from middle-to-low socioeconomic status homes. Also, the Child Behaviour Questionnaire-Very Short Form was administered to obtain temperament reports from parents and teachers. We will compare the parent's and teacher's reports on temperament using Mann–Whitney U-tests. Finally, multiple linear regression analyses will be conducted to explore how parent and teacher reports of temperament predict non-verbal ability. Each temperament dimension will be analysed separately. Results should be interpreted considering the low sample size.
Keywords: Ciencias Sociales; Psicología